Quantifying the effects of extreme events and oceanographic variability on the spatiotemporal biomass and distribution of two key euphausiid prey species - Evans, Rhian; English, Philina A.; Gauthier, Stéphane; Robinson, Clifford L.K. (Frontiers in Marine Science, 2023)
Euphausiids form a critical component of oceanic food chains and individual species vary in their responses to perturbation events. Using a long-term dataset from the northeast Pacific Ocean, we analyzed the complex spatial and temporal environmental variability that drives the biomass and distribution of euphausiids in spring in an important commercial fishing area. We aimed to establish if patterns of fine scale oceanographic variability and larger-scale climate events such as marine heatwaves (MHWs) could be linked with spring variability in the biomass of two key forage species in the northeast Pacific Ocean, Euphausia pacifica and Thysanoessa spinifera. To achieve this, we first quantified long-term signals of variability in fine-scale oceanographic conditions on the west coast of Vancouver Island using multivariate analysis, and then used geostatistical spatiotemporal modelling to quantify the effects on species-specific euphausiid biomass. Oceanographic data showed that the effects of warm events are not always observable, and effects vary even across small spatial scales. Warming due to the 2014-2016 MHW was relatively mild on the continental shelf (<1°C above climatology). Spring biomass of euphausiids, particularly E. pacifica, peaked in 2015, and all euphausiid groups analysed (E. pacifica, T. spinifera and total euphausiids) exhibited significant correlations with positive phases of the Pacific Decadal Oscillation. These results have implications for marine predators as euphausiids may act as system stabilisers in the northeast Pacific by preserving predator-prey relationships and therefore potentially increasing ecosystem resilience through extreme events.